Hepatic mitochondrial bioenergetics and metabolism across lactation and in response to heat stress in dairy cows* - Amy L. Skibiel (JDS Communications, 2024)
Lactation is energetically demanding for the dairy cow. Numerous morphological and metabolic changes orchestrated across different tissues in the body partition nutrients for milk synthesis. The liver is a key organ coordinating modifications in metabolism that increase substrate availability for the mammary gland. Impaired capacity to make the needed physiological adjustments for lactation, such as occurs with heat stress, can result in metabolic disease and poor lactation performance. At the cellular level, increases in mitochondrial density and bioenergetic and biosynthetic capacity are critical adaptations for successful lactation, providing energy and substrates for milk synthesis. Mitochondria are also involved in coordinating adaptation to a variety of stressors by providing the metabolic foundation to enlist a stress response. Heat stress can damage mitochondrial structures and impair mitochondrial function, with implications for pathogenesis and production. This systematic review focuses on the hepatic mitochondrial adaptations to lactation and the mitochondrial responses to heat stress. Future research directions are also discussed that may lead to improvements in managing the metabolic needs of the lactating cow and diminishing the adverse production and health consequences from environmental stress.